Prolonged Postoperative Vasoplegia in Pediatric Patients on Chronic Angiotensin II Blocker Treatment - Pandya, Nischal R.; Alphonso, Nelson; Tu, Quyen; Venugopal, Prem; Schlapbach, Luregn J. (Frontiers in Cardiovascular Medicine, 2018)
Prolonged postoperative vasoplegia is known to occur following cardiac surgery in patients on chronic angiotensin II receptor blocker (ARB) treatment in adults. The perioperative management of these drugs in the paediatric population is not well described and here we would like to highlight this fact. While ARBs are increasingly used in children and adolescents with hypertension, there is lack of data to guide optimal pre-surgical management in the pediatric age group. We report two cases of prolonged vasoplegia following cardiopulmonary bypass occurring in adolescent patients on chronic ARB therapy and the importance of cessation of these drugs preoperatively.